European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on Macroprudential Oversight and the Role of the ESRB. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This article reviews the European Systematic Risk Board (ESRB), its role, approach, outputs, and effects in the European Union. The ESRB is the reason for macroprudential oversight of financial systems. Macroprudential policy is used to identify and reduce financial risks and limit financial imbalances. This policy is for both upturns and downturns of economic cycles. The role of the ESRB should be further enhanced to cover the entire financial system and institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet